3-D Visualization And Standardization Of GIS Elements For Pollution Monitoring Of Water Resources - Mitreski, Kosta; Stevkovski, Stojan; Davchev, Dancho (My University, 2004)
The old legislation concerning water policy didn’t provide a standardized way of integrating our environmental protection objectives. A significant progress in this direction is expected by applying the Water Framework Directive (WFD), together with the guidance document for implementing GIS elements within WFD. In this paper, we will present how the critical pollution sources in the Lake Ohrid can be presented and analysed by using visualization methods. We will also present our approach in adaptation of Web-based GIS for pollution monitoring (WGISPM) of Lake Ohrid to the WFD (case study).The whole project is under construction.